Anger and psychological symptoms relationship: mediator role of maladaptive schemas - Özmen, Ahmet (Frontiers in Psychology, 2023)
Trait anger is the strong predictor of various psychological symptoms like anxiety, depression, and hostility. Explaining how and why this relationship occurs is crucial to come up with more effective prevention and intervention strategies in the field. To this end, the current study aimed to reveal the mediating effect of early maladaptive schemas, which is the basic concept of schema therapy, on the relations of trait anger and psychological symptoms. Data was collected from 301 university students by using the measurement tools of Brief Symptom Inventory, Trait Anger Scale and Young Schema Scale. Findings revealed that trait anger positively predicted psychological symptoms. Secondly, a set of predictive models were prepared to detect the mediating effect of early maladaptive schemas. According to the analysis in the last stage, early maladaptive schemas fully mediated the relationship between trait anger and psychological symptoms.